The Humanism of Authorities in Realizing Community Welfare in Bandar Lampung City - Dharmayani; Fathul Mu’in; Rudi Santoso; M Dani Fariz Amrullah D; Hendriyadi (Pascasarjana IAIN Metro, 2025)
This study examines the roles of the Bandar Lampung City Police and District Attorney's Office in ensuring legal certainty and public benefit. As field research, data was gathered directly from these institutions, utilizing a qualitative approach that does not involve statistical testing. Findings reveal that the Police contribute to legal certainty and economic recovery through maintaining security and public order, enforcing the law, distributing social assistance, and conducting routine patrols. The District Attorney's Office supports economic recovery through prosecution and legal assistance roles. However, challenges like limited human resources and community support hinder optimal performance. Both institutions operate under positive law (Police: Article 13 of Law No. 2 of 2002; District Attorney's Office: Article 2 of Law No. 16 of 2004) and align with Islamic principles of Fiqh Siyasah Tanfidziyah, ensuring their actions adhere to both statutory and Islamic law.